Bridging Practice and Learning: A Content Analysis of Student Internship Experiences in Hospitality and Transportation Sectors - Oktawirani, Panca; Fitrianda, Meilina Indah; Sartika, Yulia (Universitas Pendidikan Indonesia (UPI), 2025)
Internships serve as a critical component of tourism and hospitality education, offering students the opportunity to apply theoretical knowledge in real-world settings. This study conducts a qualitative content analysis of two diploma student internship reports, focusing on placements at the international chain hotel and local tourism transportation. The analysis reveals four key thematic areas: task performance and role clarity, professional behavior and service ethics, technological adaptation, and reflections on learning and career readiness. Findings indicate that while students gained valuable operational experience and service skills, there was limited evidence of structured reflection and mentoring as the elements crucial for maximising learning outcomes and employability. This study contributes to the discourse on work-integrated learning by highlighting the need for improved internship design, including feedback mechanisms and alignment with digital and soft skill development. Implications are discussed for educators, industry partners, and policymakers aiming to enhance the effectiveness of vocational training in tourism education.